Perumusan Staregi Bisnis untuk Perusahaan Youngsterpro dalam Rangka Meningkatkan Kinerja - Fenty Febrianty (Universitas Tarumanagara, 2019)
This research was conducted to help Youngsterpro companies determine appropriate business strategies in order to improve performance. This study applies qualitative methods through field research to the parties concerned in obtaining information, besides that also based on literature studies and analytical methods in strategy formulation here consists of three stages, the input by analyzing SWOT, EFE matrix, IFE matrix to summarize the basic information used to produce an alternative strategy in Matching stage, is the second stage, by aligning external and internal factors using the SWOT matrix and SPACE matrix, and the last is the decision making stage to determine the best strategy for the company based on the attractiveness of each strategy objectively through the QSPM matrix . The results of the study recommend Youngsterpro companies to consider a diversification strategy because it is the best strategy that is most appropriate for Youngsterpro besides that the product development strategy can also be considered as an alternative strategy to improve performance.